Fatal Hemorrhage From AVM After DBS Surgery: Case Report. Issue 5 (11th October 2012) - Fukaya, Chikashi; Shimoda, Kentaro; Watanabe, Mitsuru; Morishita, Takashi; Sumi, Koichiro; Otaka, Toshiharu; Obuchi, Toshiki; Toshikazu, Kano; Kobayashi, Kazutaka; Oshima, Hideki; Yamamoto, Takamitsu; Katayama, Yoichi
<x xml:space="preserve">Abstract</x> Objectives Intracranial hemorrhage is a crucial complication of deep brain stimulation (DBS) surgery. The bleeding caused by mechanical tissue injury due to microelectrode and/or DBS electrode lead insertion has been well studied. However, hemorrhage caused by a congenital underlying disease such as vascular malformation has not been examined carefully. Materials and Methods We encountered a case of intracerebral hemorrhage from arteriovenous malformation (AVM) after DBS surgery. Preoperative magnetic resonance (MR) imaging did not show any abnormality in the patient. Computed tomography (CT) images taken immediately after the surgery did not show any intracranial hematoma and other abnormal findings. However, the patient did not recover from the general anesthesia, and hemorrhage in the left occipital lobe was detected by CT performed a day after the surgery. The location of the hematoma was markedly distant from the trajectory of DBS leads. Evacuation of the hematoma under general anesthesia was immediately performed. Results As an intraoperative finding, we noted the presence of abnormal vessels inside the hematoma in the occipital lobe. Tissue specimens including the abnormal vessels were obtained for histopathological analysis, results of which led to the diagnosis was AVM. Conclusion Despite its low incidence, we would like to advise that such a type of hemorrhage could occur and measures should be taken to prevent its occurrence as much as possible. Preoperative detection of abnormal vessels by MR angiography and/or CT angiography might be helpful. Moreover, paying close attention to the possible leakage of cerebrospinal fluid during surgery might be important.